PERBEDAAN LEBAR GIGI ANTERIOR RAHANG ATAS DENGAN KONSEP GOLDEN PROPORTION PADA MAHASISWA FKG UNIVERSITAS ANDALAS SUKU MINANG - Riani Hafiza; Fadil Oenzil; Murniwati Murniwati (Faculty of Dentistry Universitas Andalas, 2015)
Background: One of the parameter that can represent the ideal beauty is the concept of the golden proportion. The proportion on teeth can be seen from frontal view. The width of the central incisor is 62% wider than the width of the lateral incisor. The width of the lateral incisor is 62% wider than the visible part of canine. One of the factors that affect the size of the tooth is race. Minang ethnic is included to Malay Deutro. Purpose: The purpose of this study is to determine the difference of the width of maxillary anterior teeth with the concept of the golden proportion in Minang ethnic students of Faculty of Dentistry, Andalas University. Methods: The study was an analytic observasional with cross-sectional approach. The sampling was purposive sampling and the number of subjects were 26 respondents. Photographs of the respondents were taken at least three times each using a digital camera Sony Cyber-shot DSC-S3000 10.1 MP, edited using software Adobe Photoshop CS5 and analyzed using paired sample t test. Result: The result of paired sample t test is p=0.000 (p<0.05). This suggests there is a significant difference between the width of maxillary anterior teeth with the concept of the golden proportion in Minang ethnic students of Faculty of Dentistry, Andalas University. The proportion of the width of maxillary anterior teeth from the frontal view according to golden proportion 1.62 : 1 : 0.62, when it comes to Minang ethnic students of Faculty of Dentistry, Andalas University, it is measured as 1.51 : 1 : 0.76 for right region and 1.52 : 1 : 0.77 for left one. Conclusion: The concept of the golden proportion can not be used to Minang ethnic students of Faculty of Dentistry, Andalas University. Keywords: aesthetic, anterior teeth, golden proportion, maxillary, Minang ethnic